2011
DOI: 10.1016/j.bmc.2011.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Trace amine-associated receptor 1 is a stereoselective binding site for compounds in the amphetamine class

Abstract: The demonstrated ability of amphetamine to functionally activate the rat trace amine associated receptor 1 (rTAAR1) and the subsequent reports of amphetamine activation of TAAR1 in rhesus monkey mouse, human, and human-rat chimeric TAAR1-expressing cell lines has led to speculation as to the role of this receptor in the central nervous system (CNS) responses associated with amphetamine and its analogs. The agonist potencies of ten pairs of enantiomeric amphetamines, including several with known CNS activity, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 36 publications
1
15
0
1
Order By: Relevance
“…The in vitro pharmacology of comparator compounds and some psychoactive substances (amphetamine, methamphetamine, MDMA) were previously determined by us and others (Borowsky et al, 2001;Bunzow et al, 2001;Reese et al, 2007;Wainscott et al, 2007;Lindemann et al, 2008;Lewin et al, 2011). The replication of those data for this study was an important validation of our assays.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The in vitro pharmacology of comparator compounds and some psychoactive substances (amphetamine, methamphetamine, MDMA) were previously determined by us and others (Borowsky et al, 2001;Bunzow et al, 2001;Reese et al, 2007;Wainscott et al, 2007;Lindemann et al, 2008;Lewin et al, 2011). The replication of those data for this study was an important validation of our assays.…”
Section: Discussionsupporting
confidence: 54%
“…One limitation of our study is that we did not consider stereoselectivity of the compounds by screening racemic mixtures for most substances. As with activity at other psychostimulant targets, such as monoaminergic reuptake transporters, TAAR1 has a stereoselective binding site, and the assessment of racemates could underestimate the activity of the more active isomer (Lewin et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…At higher doses, (S)‐(+)‐amphetamine has stimulant properties that are stronger than R‐(−)‐amphetamine, and increases dopamine activity. Hence, (S)‐(+)‐amphetamine is several times more potent than the R‐(−)‐enantiomer in eliciting central nervous system effects . Also, the R‐(−)‐amphetamine produces more cardiovascular and peripheral effects than the (S)‐(+)‐amphetamine .…”
Section: Introductionmentioning
confidence: 99%
“…It was first observed by Bunzow et al (2001) 4 and then further expanded by Reese et al (2007) 12 and Lewin et al (2011) 37 that amphetamine and amphetamine-like drugs were pharmacological agonists at TAAR1. Wolinsky et al (2007) 17 and Lindemann et al (2008) 18 reported that deletion of the TAAR1 gene in mice results in the pharmacogenic phenotype of an enhanced locomotive response to amphetamine, coincident with an amphetamine-induced increase in the release of biogenic amines.…”
mentioning
confidence: 96%